Diretrizes de projeto para desempenho térmico de sistemas de paredes pré-moldadas de concreto - Raeder, Laylah Regina (2018)
The industrialized precast building systems have been used all over the world in housing construction since the 50’s. In Brazil, as there were no specific standard codes for precast panels until 2016, the use of those building systems have been under the certification of technical evaluations called DATec from the SINAT system. Since the approval of the new code of practice NBR16475:2017 - Wall Precast Panels and the review of NBR9062:2017, many performance aspects related to structural safety, fire, water tightness, among others are now covered, however there is not yet a very clear position regarding thermal performance requirements. In this context, as specific contribution, this research intends to present the results of an exploratory study regarding aspects and design conditions related to precast walls’ thermal performance, according to the code of practice ABNT NBR 15575 and the precast code of practice ABNTNBR 16475. In order to potentialize a greater usability of those systems in Brazil, this study was accomplished through the measurement of the wall surface temperature using a thermal camera and the comparison of the achieved numbers, verifying the importance of design factors that influence the façade's temperature variation through the solar energy absorption at heat flow, impacting wall panel's thermal performance.